2013
DOI: 10.1186/cc13114
|View full text |Cite
|
Sign up to set email alerts
|

Clinical review: Lung imaging in acute respiratory distress syndrome patients - an update

Abstract: Over the past 30 years lung imaging has greatly contributed to the current understanding of the pathophysiology and the management of acute respiratory distress syndrome (ARDS). In the past few years, in addition to chest X-ray and lung computed tomography, newer functional lung imaging techniques, such as lung ultrasound, positron emission tomography, electrical impedance tomography and magnetic resonance, have been gaining a role as diagnostic tools to optimize lung assessment and ventilator management in AR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 98 publications
(136 reference statements)
0
56
0
2
Order By: Relevance
“…[88][89][90][91] CT imaging has long been the accepted standard for assessments of alveolar recruitment and overdistention. Digital chest radiography done at the bedside with PEEP of 5 and 15 cm H 2 O might also be useful to detect recruited lung volume.…”
Section: Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…[88][89][90][91] CT imaging has long been the accepted standard for assessments of alveolar recruitment and overdistention. Digital chest radiography done at the bedside with PEEP of 5 and 15 cm H 2 O might also be useful to detect recruited lung volume.…”
Section: Imagingmentioning
confidence: 99%
“…The ultrasound pattern corresponds to the degree of lung aeration. 88,[93][94][95][96] This allows the potential for the use of ultrasound to monitor the response to recruitment maneuvers and PEEP titration (Fig. 9).…”
Section: Imagingmentioning
confidence: 99%
“…Since 1980, CT has been used to study the inhomogeneous pattern of lung lesions in ARDS. 52 Since CT study of the lung parenchyma has led to major findings in ARDS comprehension, in this review, we reported data from follow-up CT scan studies. Four CT abnormalities were found in ARDS subjects, based on the Fleischner Society Glossary: (1) ground glass opacity (defined by a hazy increase in lung attenuation with preservation of bronchial and vascular margins); (2) consolidation or intense parenchymal opacification in the previously published glossary of the society (defined by a homogeneous increase in pulmonary parenchyma attenuation that obscures the margins of vessels and the airway wall); (3) reticular pattern (defined by a collection of innumerable small linear opacities, constituted by interlobular septal thickening, intralobular lines, or the cyst walls of honeycombing); and (4) decreased attenuation (which includes emphysema and small airways disease).…”
Section: Radiological Findingsmentioning
confidence: 99%
“…MR lung tissue imaging was used to image the elastic properties of lungs with ventilator-induced lung injury in rats (76) and to study the physiopathology and the progress of lung injury. Furthermore, morphological and pathophysiological patterns like 'ground-glass opacification' and 'consolidation' in ARDS could be detected by MRI similarly as with CT (75). A recent work in rats demonstrated that lung MRI can detect small regions of ventilator-induced injury earlier than the appearance of alterations in lung mechanics in rats, this finding was confirmed with histology and the authors also demonstrated the possibility of visualizing and quantifying the regression of injury in real-time, after adoption of protective mechanical ventilation strategies (77).…”
Section: Mrimentioning
confidence: 98%
“…MRI enables calculation of alveolar size based on the MRI apparent diffusion coefficient (73), and this has a potential application to determine the consequences of atelectasis and recruitment manoeuvres (70). Gases with fast spin-rotation relaxation at thermal equilibrium polarization have been used to study differences in ventilation-perfusion ratio (74) and time constants for fast and slow filling lung compartments, giving information about ventilation-perfusion heterogeneity, pulmonary endcapillary diffusion of oxygen and lung microstructure in ARDS (75). Visualization of ventilation is also possible using oxygen-enhanced MRI (72).…”
Section: Mrimentioning
confidence: 99%